2021
DOI: 10.1021/acs.jafc.0c08119
|View full text |Cite
|
Sign up to set email alerts
|

A Piperine-Based Scaffold as a Novel Starting Point to Develop Inhibitors against the Potent Molecular Target OfChtI

Abstract: The insect chitinase Of ChtI from the agricultural pest Ostrinia furnacalis (Asian corn borer) is a promising target for green insecticide design. Of ChtI is a critical chitinolytic enzyme for the cuticular chitin degradation at the stage of molting. In this study, piperine, a natural amide compound isolated from black pepper, Piper nigrum L., was discovered for the first time to have inhibitory activity toward Of ChtI. The compound−enzyme interaction was presumed to take place between the piperine benzo [d][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 60 publications
2
57
0
2
Order By: Relevance
“…More notably, the insecticidal activity of Compound 5k was even equivalent to the positive control tebufenozide to some extent. Moreover, Compound 5k was detected to exhibit equivalent or even better insecticidal activity against the Asian corn borer at a lower concentration than the excellent single-chitinase inhibitors butenolide derivatives and the dual-chitinase inhibitor anacardic acid reported in previous studies, 21,35 although the inhibitory activity of Compound 5k against each chitinase was not the most prominent. It is obvious that the multichitinase inhibitor indeed demonstrated better insecticidal activity than those dual-or single-chitinase inhibitors, suggesting that it exhibits better advantages in the control of the Asian corn borer.…”
Section: Stomach-toxicity Insecticidal Activity Evaluation Of Novel P...mentioning
confidence: 73%
See 3 more Smart Citations
“…More notably, the insecticidal activity of Compound 5k was even equivalent to the positive control tebufenozide to some extent. Moreover, Compound 5k was detected to exhibit equivalent or even better insecticidal activity against the Asian corn borer at a lower concentration than the excellent single-chitinase inhibitors butenolide derivatives and the dual-chitinase inhibitor anacardic acid reported in previous studies, 21,35 although the inhibitory activity of Compound 5k against each chitinase was not the most prominent. It is obvious that the multichitinase inhibitor indeed demonstrated better insecticidal activity than those dual-or single-chitinase inhibitors, suggesting that it exhibits better advantages in the control of the Asian corn borer.…”
Section: Stomach-toxicity Insecticidal Activity Evaluation Of Novel P...mentioning
confidence: 73%
“…The stomach toxicities of all compounds against O. furnacalis were evaluated by the leaf-dip method using reported procedures. , Maize leaves were dipped into a test solution (5% DMSO solution of tested compounds and 0.2% Tween-90 in distilled water) for 5 s. After air-drying, three treated leaves were placed into a petri dish and infested with 20 3rd-instar larvae of O. furnacalis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu and Yang, (2017 ) found that piperine derivatives show stomach toxicity activity against agricultural pests with effects comparable to the commercial botanical pesticide toosendanin (CN107892685A). Han et al (2021 ) designed a series of compounds that combined the benzo[ d ][1,3]dioxole moiety of piperine, which showed effective insecticidal activity against Ostrinia furnacalis .…”
Section: Introductionmentioning
confidence: 99%